2019
DOI: 10.1002/clen.201900047
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Banana Stem Juice as a Feedstock Material for Bioethanol Production

Abstract: Bananas are widely cultivated in tropical and subtropical countries and about 220 tons of biomass waste is produced per hectare of banana plantation. Banana pseudostem contains nearly 90% of moisture and about 4-5 m 3 sap is generated from one ton of dried stem with high chemical oxygen demand(COD) and biological oxygen demand (BOD). The feasibility of using banana sap as a feedstock to produce ethanol is evaluated in this study. Banana sap is obtained by crushing the pseudostems and concentrated ten times and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[ 53,232 ] Gupta et al. [ 246 ] and Razaghi et al. [ 243 ] used HCl instead of H 2 SO 4 to prevent the formation of furfural and hydroxymethylfurfural.…”
Section: Processing Of Fvwmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 53,232 ] Gupta et al. [ 246 ] and Razaghi et al. [ 243 ] used HCl instead of H 2 SO 4 to prevent the formation of furfural and hydroxymethylfurfural.…”
Section: Processing Of Fvwmentioning
confidence: 99%
“…[ 232,249–251 ] However, Gupta et al. [ 246 ] carried out acid and basic hydrolysis of banana residues in parallel to check the effectiveness of these treatments in terms of fermentable sugars. The results showed that acid hydrolysis is more effective for sugar extraction when comparing the two methods, obtaining more than 8 g L −1 of sugar content from acid pre‐treatment and ≈7 g L −1 of sugar content from alkali hydrolysis.…”
Section: Processing Of Fvwmentioning
confidence: 99%
See 1 more Smart Citation
“…This Musa acuminata peduncle juice extract can be used to solve the mild steel corrosion problem in seawater and the associated issues in several scenarios. Additionally, it is worth mentioning that Musa acuminata peduncle juice has high amounts of several bioactive substances, 14 helps make biodiesel, 15 and has healing properties, 16 to name a few. However, there is little or no information on the inhibition properties and potential of M. acuminata peduncle juice on mild steel.…”
Section: Introductionmentioning
confidence: 99%
“…After harvesting the bananas, the plant dies. The dead plants comprising of leaves, pseudo-stems contribute to huge agro-waste from the banana farms into the environment (Gupta et al 2019 ). Moreover, the pseudo-stem of banana is finding application in the paper manufacturing industry along with a wide range of value-added products such as ropes, mats etc.…”
Section: Introductionmentioning
confidence: 99%